“Sistema de control interno para inventarios en el “Centro Comercial Noble” del cantón La Maná”. - Pallo Pallo, Margoth Leticia (2020)
The application of internal control is projected to be a very useful tool to improve the performance of the inventory control function, that is why, it was proposed as a general objective to design an internal control system for inventory management in the supermarket “Noble” in La Maná canton that allows increasing the effectiveness of inventory control and management. The methodology used was exploratory, descriptive research, scientific and analytical research methods, through the use of direct observation techniques, interviews and surveys aimed at company personnel through the application of surveys and interviews to personnel. The company identified that the commercial establishment does not have policies and procedures, which makes it difficult to control the merchandise properly; there is a risk that the products will deteriorate due to the time stored in the warehouse. In response, an analysis of the current situation of the supermarket “Noble” was developed. In its preliminary diagnosis through a SWOT analysis, it was established that its main strengths constitute the variety of products it offers and the price level it handles in all its product lines, while one of their most important weaknesses turned out to be the management of their inventories, due to a weak internal control of inventories. The evaluation of internal control, allowed to identify the critical areas of the company and determine findings such as the absence of policies and procedures in the area of inventories and sales, no conditions have been defined for the return of products, does not have a policy manual for the cash area, there is no process of induction and training of personnel, inadequate product reception system. The following risk levels have been determined: 40% for the sales area, 17% for the purchasing area, 25% for the human resources area, and 20% for the inventory area. Therefore, it was proposed a manual of functions, policies and procedures based on the evaluation of the internal control system and structural organizational chart of the company, 20% for the area of inventories, which when applied seeks to directly benefit the owners, employees, and customers of the supermarket Noble in La Maná.